Quantitative evaluation of pytocompounds from Terminalia Chebula by high performance thin layer chromatography (HPTLC) method and its antibiofilm activity (Funded work) - DR.T.SAVITHA, (International Journal of Pharma and Bio Sciences, 2017)
The efficacy of phytocompounds such as tannic acid (TA) and ellagic acid (EA) from dried fruits of Terminalia chebula Retz against Multiple Drug Resistant Uropathogenic Escherichia coli (MDRUPEC) by using High Performance Thin Layer Chromatography (HPTLC) and by Confocal Laser Scanning Microscopy (CLSM) techniques. The effectiveness of these phytoconstituents against biofilm formation has been studied in which methanol extract of T.chebula have shown best activity against biofilm forming organisms compared to other standard compounds. Due its paramount action, the qualitative and quantitative evaluation of its phytocompounds was made by using HPTLC analysis. Simultaneously, anti-biofilm activity of these phytocompounds have also be evaluated against MDRUPEC with CLSM technique. The present research has shown that, amongst an assortment of concentrations of the plant extracts used, 40µg/ml has exhibit best antibacterial activity against the test strains. The evaluation of phytocompounds such as Gallic Acid (GA), Tannic Acid (TA) and Ellagic Acid (EA) were quantitatively estimated 279.42 ng (nanogram), 16.13 µg (microgram) and 22.00 µg respectively by using HPTLC method. This newer approach have formed a frame work for development of new phytochemical therapeutic agents for the effective treatment of various alarming diseases of human population by the drug resistant microbes.